Digital Business Transformation through Shopee’s Integrated Strategy in Global E-Commerce - Andayani, Dwi; Ubed, Roby Syaiful; Pranata, Sudadi; Hikam, Ihsan Nuril; Kamal, Abdullah Arif (ADI Bisnis Digital Interdisiplin Jurnal, 2025)
In the rapidly evolving landscape of global e-commerce, businesses are compelled to undergo digital transformations to remain competitive. This study delves into the digital business transformation journey of Shopee, a prominent player in the e-commerce realm, focusing on its integrated strategy amidst the global market. Despite extensive research on digital marketing, there remains a gap in comprehending how digital marketing strategies, customer experience, technological innovation, and digital marketing engagement synergize within the context of Shopee’s digital ecosystem. This study aims to address this gap by analyzing the interplay between these variables and their impact on digital marketing engagement. Employing Structural Equation Modeling (SEM) using SmartPLS version 4, the research scrutinizes key variables, namely Digital Marketing Strategies, Customer Experience, Technological Innovation, and Digital Marketing Engagement. The analysis is supported by insights synthesized from academic literature, industry reports, and empirical data. The findings provide valuable insights into how the integration of digital marketing strategies, technological innovation, and customer experience contributes to strengthening digital marketing engagement within Shopee’s platform. This study offers important implications for practitioners and scholars navigating the complexities of digital business transformation. However, while acknowledging the significance of these findings, it is important to note the study’s limitations, including sample size and potential biases inherent in self-reported data. Nevertheless, this research contributes to the ongoing discourse on digital marketing strategies by offering a nuanced understanding of the multifaceted dynamics shaping the global e-commerce landscape.